2018
DOI: 10.1002/jor.24072
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐objective design optimization of high tibial osteotomy for improvement of biomechanical effect by using finite element analysis

Abstract: Medial opening wedge high tibial osteotomy (HTO) makes the proximal tibia a highly unstable structure and causes plates and screws to be the potential sources for mechanical failure. However, asymmetrical callus and incomplete bone formations underneath the plates (TomoFix) have been recent concerns in clinical and experimental studies related to HTO due to the high stiffness. The purpose of this study was to evaluate the biomechanical effect of the TomoFix plate system with respect to changes in design using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The FE has previously been used to investigate various elements of HTO: plate type and construct stability 10,19‐22 and to optimise mechanical axis positioning 23 . Where FE models have previously been used to investigate apical drill holes, only stresses have been examined and results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FE has previously been used to investigate various elements of HTO: plate type and construct stability 10,19‐22 and to optimise mechanical axis positioning 23 . Where FE models have previously been used to investigate apical drill holes, only stresses have been examined and results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect different volumes of bone occupying the ROI rather than a truly significant difference between 10 mm and 7.5 mm scenarios. The FE has previously been used to investigate various elements of HTO: plate type and construct stability 10,[19][20][21][22] and to optimise mechanical axis positioning. 23 parison.…”
Section: Boundary Conditions and Loadingmentioning
confidence: 99%
“…The optimum design provides the best performance with respect to a given performance condition and simultaneously satisfies any design space limitations [25]. Recently, Koh et al evaluated the biomechanical effect of the TomoFix plate system with respect to different plate designs using a computational simulation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that an optimal design demonstrated the feasibility of design optimization and improvements in biomechanical stability for long plate [26]. However, there has been no study for short plate to overcome its disadvantage by design optimization.…”
Section: Introductionmentioning
confidence: 99%
“…FE has previously been used to investigate various elements of HTO: plate type and construct stability 11,[20][21][22][23] and to optimise mechanical axis positioning 24 . Where FE models have previously been used to investigate apical drill holes, only stresses have been examined and results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%